Rolling-out Lean in the Saskatchewan Health Care System: Politics Derailing Policy - Tom McIntosh (McMaster University Library Press, 2016)
Following on the work of Marchildon (2013) this paper examines the political challenges faced by the government of Saskatchewan in rolling out their Lean reforms to the entire provincial health system. The government's Lean reforms were meant as a vehicle to empower patients and workers in the redesign of service delivery and the creation of a patient-centred system. Lean focuses on continuous improvement, priority setting, employee engagement and the elimination of waste. The reforms appear to have been derailed to a significant degree insofar as key actors inside the system, the media and the public have challenged the goals of the reform, the Lean methodology and process, as well as the cost of the consultants employed to oversee the process. The government's implementation of the roll-out suffered both from the ability of key actors to withdraw their support and challenge the viability of the reforms in public as well as from a public relations perspective that put the government on the defensive about how people inside the system were being treated with the reforms. As the government moves forward it will have to adjust its implementation processes and strategy in order to overcome the now strong resistance within the health sector.